2013
DOI: 10.1371/journal.pone.0072027
|View full text |Cite
|
Sign up to set email alerts
|

Myosin7a Deficiency Results in Reduced Retinal Activity Which Is Improved by Gene Therapy

Abstract: Mutations in MYO7A cause autosomal recessive Usher syndrome type IB (USH1B), one of the most frequent conditions that combine severe congenital hearing impairment and retinitis pigmentosa. A promising therapeutic strategy for retinitis pigmentosa is gene therapy, however its pre-clinical development is limited by the mild retinal phenotype of the shaker1 (sh1−/−) murine model of USH1B which lacks both retinal functional abnormalities and degeneration. Here we report a significant, early-onset delay of sh1−/− p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 60 publications
3
33
0
1
Order By: Relevance
“…This includes 18 loss-of-function and other variants in MYO7A and ABCA4 that affect codons known to cause disease when altered in humans (Molday et al 2009;Millán et al 2011). These codon-specific mutations are particularly valuable in rhesus macaques because this species models human retinal disease more closely than rodent models (Lillo et al 2003;Coleman et al 2004;Francis et al 2008;Colella et al 2013). Across a variety of physiological systems, human genetic mechanisms can be modeled more effectively in primates than in other species (Barr et al 2004;Loffredo et al 2007;Vallender et al 2010;Rogers et al 2013;Phillips et al 2014); thus, functional variants in macaque genes orthologous to human disease genes (eye diseases or others) will provide significant and unique opportunities to model genetic mechanisms or test therapies for those disorders.…”
Section: Functional Annotation Of Rhesus Snvsmentioning
confidence: 99%
“…This includes 18 loss-of-function and other variants in MYO7A and ABCA4 that affect codons known to cause disease when altered in humans (Molday et al 2009;Millán et al 2011). These codon-specific mutations are particularly valuable in rhesus macaques because this species models human retinal disease more closely than rodent models (Lillo et al 2003;Coleman et al 2004;Francis et al 2008;Colella et al 2013). Across a variety of physiological systems, human genetic mechanisms can be modeled more effectively in primates than in other species (Barr et al 2004;Loffredo et al 2007;Vallender et al 2010;Rogers et al 2013;Phillips et al 2014); thus, functional variants in macaque genes orthologous to human disease genes (eye diseases or others) will provide significant and unique opportunities to model genetic mechanisms or test therapies for those disorders.…”
Section: Functional Annotation Of Rhesus Snvsmentioning
confidence: 99%
“…component (12)(13)(14)(15). These experimental conditions fail to recapitulate the cellular and molecular environment of diseased photoreceptors in patients who have a complex spatial distribution of stages of disease across the retina (Fig.…”
Section: Significancementioning
confidence: 99%
“…Moreover, following injection into the subretinal space of Myo7a sh1-4626SB mice, MYO7A could be detected at WT levels in the RPE and photoreceptor cells, and at higher levels with more concentrated virus (Lopes et al 2013). Western blot analysis of posterior eye segments, after subretinal injection, showed that expression persists for at least 15 mo (Colella et al 2013). Two separate studies have shown that mutant retinal phenotypes of Myo7a sh1-4626SB mice could be rescued both in the RPE and photoreceptors.…”
Section: Aav Single Vectorsmentioning
confidence: 98%
“…Studies on the ability of oversized AAV vectors to generate MYO7A in HEK293 cells (Colella et al 2013) and RPE primary cultures derived from Myo7a sh1-4626SB mice (Lopes et al 2013) showed that they can indeed produce full length protein, with no major evidence of truncated products. In the RPE cultures from Myo7a sh1-4626SB mice, the expression level of MYO7A was comparable to that in cultures from heterozygous control littermates.…”
Section: Aav Single Vectorsmentioning
confidence: 99%
See 1 more Smart Citation